2020
DOI: 10.1126/sciadv.abb0205
|View full text |Cite
|
Sign up to set email alerts
|

GADD34 is a modulator of autophagy during starvation

Abstract: Cells respond to starvation by shutting down protein synthesis and by activating catabolic processes, including autophagy, to recycle nutrients. This two-pronged response is mediated by the integrated stress response (ISR) through phosphorylation of eIF2α, which represses protein translation, and by inhibition of mTORC1 signaling, which promotes autophagy also through a stress-responsive transcriptional program. Implementation of such a program, however, requires protein synthesis, thus conflicting with genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The PPP1R15A gene mediated cell growth arrest and apoptosis in response to DNA damage (Wu et al, 2002). It has shown its induced effect on autophagy through the suppression of the mTOR pathway during starvation (Uddin et al, 2011;Gambardella et al, 2020). We did not find any effects of this gene on testicular function in the literature.…”
Section: Discussionmentioning
confidence: 66%
“…The PPP1R15A gene mediated cell growth arrest and apoptosis in response to DNA damage (Wu et al, 2002). It has shown its induced effect on autophagy through the suppression of the mTOR pathway during starvation (Uddin et al, 2011;Gambardella et al, 2020). We did not find any effects of this gene on testicular function in the literature.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, PERK-mediated ATF4/CHOP expression induces autophagy by inhibiting mTORC1 activity ( Salazar et al, 2009 ; Bruning et al, 2013 ). Recently, The TFEB-mediated GADD34 expression may integrate mTORC1-mediated autophagy and ER stress ( Gambardella et al, 2020 ). ER stress can also activate the CMA pathway by PERK activation, which recruits mitogen-activated protein kinase 4 (MKK4) and activates p38 to phosphorylate LAMP2A for CMA activation ( Li et al, 2017 ).…”
Section: Interplay Of Er Stress and Autophagymentioning
confidence: 99%
“…PPP1R15A is involved in apoptosis following ionizing radiation [ 59 ], methyl-methanesulfonate treatments [ 60 ], and in endoplasmic reticulum stress [ 58 ]. In 2020, Gambardella et al [ 61 ] found that PPP1R15A also plays an essential role in autophagy, by enabling lysosomal biogenesis and a sustained autophagic flux [ 61 ]. In fact, PPP1R15A is also essential for translation during starvation [ 61 ] but also in apoptosis, if the endoplasmic reticulum stress is not resolved [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Gambardella et al [ 61 ] found that PPP1R15A also plays an essential role in autophagy, by enabling lysosomal biogenesis and a sustained autophagic flux [ 61 ]. In fact, PPP1R15A is also essential for translation during starvation [ 61 ] but also in apoptosis, if the endoplasmic reticulum stress is not resolved [ 62 ]. Therefore, PPP1R15A plays a crucial role in both autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%